PERFORMING CORPORATE BODIES multinational theatre in global india. - Saddler, Sarah ([S.l.] : ROUTLEDGE, 2025)
This book offers the first look at corporate theatre, a global management trend that uses dramatic techniques in workplace learning. Drawing on a decade of research with artists, consultancies, drama schools, and multinational firms in India and across the Global South, Sarah Saddler provides a fascinating perspective on why theatre and performance are finding new legitimacy in corporate economies under late capitalism. Chapters spotlight how theatre is wielded by management to advance urgent corporate agendas, while examining corporate theatres impact on broader social transformations, such as the theatrical dimensions of management and shifting creative horizons for performance practitioners. Through vivid vignettes, Sarah Saddler argues that corporate theatre has become a mode of physical and psychological conditioning used to encode the cultural dimensions of global capitalism. Simultaneously, she uncovers how corporate theatre employs humor tactics that enable individuals to navigate systems of power, becomes a remedy for corporations grappling with the crushing competition of capitalism, and offers a critical perspective on artistic agency within the creative economy. This book will be of interest to readers across the interdisciplinary humanities including theatre and performance studies, anthropology, sociology, and South Asian studies.
Keywords: Corporate governance -- India; Executives -- India; PERFORMING ARTS / General; PERFORMING ARTS / Acting & Auditioning; PERFORMING ARTS / Theater / History & Criticism